Analysis of Accounting Information Systems for Purchase and Sales in MSMEs - Azkia Kurnia, Ramadhanti; Aryanto, .; Misinem, .; Tri Basuki, Kurniawan (INTI International University, 2023)
The current state of demand analysis, information technology development, and industrial technology utilization in the industrial sector, particularly in small and medium-sized enterprises (MSMEs), is characterized by rapidity. The analysis reveals that most MSMEs still maintain their sales records by hand, making it difficult to determine stock levels, overall sales, and earnings rapidly and accurately. To handle better records utilizing a FoxPro 9.0 database that is based on a sales accounting system, an accounting system is therefore required. To demonstrate the requirement analysis and solution, this research uses Microsoft Visual FoxPro 9.0 to create an accounting information system for purchasing and selling. The System Development Life Cycles (SDLC) technique, in conjunction with the Waterfall method, was employed in this investigation. A MySQL database is the one that is being used. Each stage of the waterfall approach will be followed in the creation of the methodology. This study results in a sales and purchases accounting system that can help with supplier purchases and sales tracking, allowing the business owner to ascertain profit margins in a matter of weeks or months. Data entry on the inventory of commodities acquired from suppliers, access to the quantity of items sold, sales reports, and reports on purchases made make up the resulting accounting information system. An accounting system for product sales and purchases can assist the business owner in learning more and making better decisions for the future management of the company.